Kajian Literatur: Pengaruh Komitmen Organisasi dan Stres Kerja terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Mediasi - Putri, Qrizzilia Izani; Saluy, Ahmad Badawi; Perkasa, Didin Hikmah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Employee turnover remains a critical challenge, particularly in high-pressure industries such as luxury fashion. This literature review investigates the influence of organizational commitment and work stress on turnover intention, with job satisfaction acting as a mediating variable. The study aims to synthesize recent empirical findings to identify consistent patterns and gaps in the relationship among these variables. A systematic review was conducted using 11 peer-reviewed journal articles published within the last ten years, selected from credible academic databases including Scopus, Google Scholar, and Emerald Insight. Articles were chosen based on their relevance, methodological rigor, and empirical focus on the key constructs. The analysis reveals that high work stress significantly increases turnover intention, while job satisfaction and organizational commitment reduce it. Moreover, job satisfaction plays a mediating role by buffering the adverse effects of stress and reinforcing commitment. The findings emphasize that organizations should strengthen employees’ emotional attachment and satisfaction to reduce turnover risks, particularly among younger generations facing high job demands. These insights provide strategic input for human resource management in designing effective retention programs and creating supportive work environments, especially within dynamic and competitive sectors.